Nitrogen-Fertilized Systems of Maize Intercropped With Tropical Grasses for Enhanced Yields and Estimated Land Use and Meat Production - Crusciol, Carlos A. C.; Mateus, Gustavo P.; Momesso, Letusa; Pariz, Cristiano M.; Castilhos, André M.; Calonego, Juliano C.; Borghi, Emerson; Costa, Ciniro; Franzluebbers, Alan J.; Cantarella, Heitor (Frontiers in Sustainable Food Systems, 2020)
Intercropping grain with forage crops bridges the gap between agriculture and sustainability. In tropical regions, forage grasses are increasingly being adopted as winter pasture intercropped and in rotation with maize to maximize food production. However, current recommendations for nitrogen (N) fertilizer application are based on monocropped maize (Zea mays), and the best N management approach for intercropping systems remains unclear. A field experiment was carried out in three growing seasons with three intercropping systems [monoculture maize, intercropped with palisadegrass (Urochloa brizantha), and intercropped with guineagrass (Megathyrus maximus)] combined with six different split applications of N to maize (0–0, 100–0, 70–30, 50–50, 30–70, and 0–100 kg N ha−1 at seeding-sidedressing) with four replicates. We measured dry matter (DM) and accumulated N in maize and forage grasses, as well as maize production components and yields. Additionally, land equivalent ratio, relative crowding coefficient, aggressivity of maize with forage grasses, forage crude protein (CP) concentration, estimated animal stocking rate, and estimated meat production and economic outcomes. Greatest maize yield was 8.7 Mg ha−1 for monocropped maize. However, favorable maize yield was also obtained in intercropping systems. Although no difference was observed between intercropping systems, applying all N at sidedressing of maize negatively affected maize and forage yields and, consequently, land use and economic evaluation. For both intercropping systems, estimated meat and land use were 114 and 10% higher when N fertilizer was applied than the control (0–0 kg N ha−1), on average. Maize-forage grass intercropping is a viable alternative production system for improving yields and land use. In addition, estimated meat production and revenue can be enhanced with palisadegrass or guineagrass. At least half of the N fertilizer must be applied early in the growing season of maize to maximize production of the entire system.